PELATIHAN DAN SERTIFIKASI ASSOCIATE WEALTH PLANNER SYARIAH (AWPS) SEBAGAI UPAYA PENINGKATAN LITERASI KEUANGAN SYARIAH PADA MAHASISWA DAN MASYARAKAT UMUM - Dina Diana (Tazkia Islamic University College, 2026)
Islamic financial literacy in Indonesia remains relatively low, especially among students and the general public. Efforts to improve Islamic financial literacy need to be carried out in a structured manner through comprehensive training and certification programs. This community service activity aims to enhance participants' understanding of Sharia-based financial planning through the Associate Wealth Planner Syariah (AWPS) Training and Certification program. The activity was held on January 29, 2026 at the International Class, 3rd Floor, Tazkia University, involving 30–50 participants from Tazkia University students and the general public. Methods used included interactive lectures, case studies, and hands-on practice using the My IFPE Syariah application. The results showed an improvement in participants' understanding of Islamic financial planning concepts, as evidenced by evaluation results and positive feedback from participants toward the trainers. Participants who passed the certification received the nationally recognized Associate Wealth Planner (AWP) designation. This activity is expected to serve as a model for Islamic financial literacy training that can be replicated on a wider scale.